Metaverso: El nuevo reto para los auditores (2023)
The metaverse is a digital environment that simulates spaces that mimic the real world allowing users to interact in it. Through the use of Virtual Reality (VR) making it easier for them to immerse themselves in digital environments using software that copies the world with the help of virtual reality helmets making them experience immersion in these new worlds;Augmented Reality (AR) modifies the vision of reality through inputs produced by an electronic device (Internet of Things - IoT) and Mixed Reality (MR) anchors the virtual objects of the world in which they live and thus can interact.